Investigation of N-Acetyltransferase 2-Mediated Drug Interactions of Amifampridine: In Vitro and In Vivo Evidence of Drug Interactions with Acetaminophen - Yeo-Dim Park; Yoon-Jee Chae; Han-Joo Maeng (MDPI AG, 2023)
Amifampridine is a drug used for the treatment of Lambert-Eaton myasthenic syndrome (LEMS) and was approved by the Food and Drug Administration (FDA) of the United States (US) in 2018. It is mainly metabolized by N-acetyltransferase 2 (NAT2); however, investigations of NAT2-mediated drug interactions with amifampridine have rarely been reported. In this study, we investigated the effects of acetaminophen, a NAT2 inhibitor, on the pharmacokinetics of amifampridine using in vitro and in vivo systems. Acetaminophen strongly inhibits the formation of 3-N-acetylamifmapridine from amifampridine in the rat liver S9 fraction in a mixed inhibitory manner. When rats were pretreated with acetaminophen (100 mg/kg), the systemic exposure to amifampridine significantly increased and the ratio of the area under the plasma concentration-time curve for 3-N-acetylamifampridine to amifampridine (AUCm/AUCp) decreased, likely due to the inhibition of NAT2 by acetaminophen. The urinary excretion and the amount of amifampridine distributed to the tissues also increased after acetaminophen administration, whereas the renal clearance and tissue partition coefficient (Kp) values in most tissues remained unchanged. Collectively, co-administration of acetaminophen with amifampridine may lead to relevant drug interactions; thus, care should be taken during co-administration.